2020
DOI: 10.3390/pathogens9080597
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Hypoxia Exposure Accelerates the Progression of Amoebic Gill Disease

Abstract: Amoebic gill disease (AGD), caused by the amoeba Neoparamoeba perurans, has led to considerable economic losses in every major Atlantic salmon producing country, and is increasing in frequency. The most serious infections occur during summer and autumn, when temperatures are high and poor dissolved oxygen (DO) conditions are most common. Here, we tested if exposure to cyclic hypoxia at DO saturations of 40–60% altered the course of infection with N. perurans compared to normoxic controls maintained at ≥90% DO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…In the current experiment, the gill samples were positive for N. perurans later than in challenges where higher concentrations of amoebae were applied (Benedicenti et al 2015;Collins et al 2017;Oldham et al 2020). There was a high variability in the severity of AGD lesions both within and between individuals and the variable size of lesions within the second left gill arch suggested that the lesions were induced at different time points or that there was high individual variability in host response to the amoeba.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In the current experiment, the gill samples were positive for N. perurans later than in challenges where higher concentrations of amoebae were applied (Benedicenti et al 2015;Collins et al 2017;Oldham et al 2020). There was a high variability in the severity of AGD lesions both within and between individuals and the variable size of lesions within the second left gill arch suggested that the lesions were induced at different time points or that there was high individual variability in host response to the amoeba.…”
Section: Discussionmentioning
confidence: 54%
“…2017; Oldham et al. 2020). There was a high variability in the severity of AGD lesions both within and between individuals and the variable size of lesions within the second left gill arch suggested that the lesions were induced at different time points or that there was high individual variability in host response to the amoeba.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system and protection against pathogens are among the main concerns. Comparisons of disease resistance in Atlantic salmon kept at normal and low levels of DO produced different results, such as absence of effect in challenge with salmon alphavirus ( Andersen et al, 2010) and accelerated progression of amoebic gill disease (Oldham et al, 2020). To our knowledge, remote effects of hypoxia on the immune system and protection against pathogens in Atlantic salmon have not been reported until present.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hypoxia appeared not to differentially affect the severity of pancreas disease in salmon infected with salmonid alphavirus (Andersen et al, 2010). On the other hand, in Atlantic salmon post-smolts infected with amoebe Neoparamoeba perurans (the agent of amoebic gill disease), cyclic hypoxia accelerated the progression of the disease and increased amoeba counts and mortality (Oldham et al, 2020). Niklasson et al (2011) showed that low DO levels affected the mucosal immune system of the intestine, through downregulations of nuclear factor kappa B, and differential expression of interleukins in combination with higher temperature.…”
Section: Introductionmentioning
confidence: 89%
“…The frequency of infection recurrence, which may necessitate multiple freshwater immersion treatments within one life cycle in the industry setting, will contribute to an elevated stress response in the fish. The resultant increase in plasma cortisol has been shown to suppress immunity, which can contribute to increased fish susceptibility and further exacerbate the issue of re-infection [ 34 , 35 ]. This work attempts to try and elucidate the response of fish re-inoculated P. perurans and to determine whether an adaptive response is initiated.…”
Section: Discussionmentioning
confidence: 99%